The dilemma of King David: Reading Josephus’ Antiquities against the grain through the lens of Greco-Roman tyrant typologies - Edwards, David R. (Journal for the study of the pseudepigrapha, 2024)
King David is the ideal Jewish monarch for Josephus no less than in the Hebrew Bible. Yet, the scriptural stories of David’s life are punctuated by dark episodes which subsequent writers and readers have struggled to integrate with their elevated vision of a noble king. In this study, I argue that the difficulties of persuading Josephus’ readers in Antiquities that the famed dynastic founder was noble, virtuous, and an ideal leader were even more exacerbated. Reading Josephus’ David against the grain of his authorial cues reveals the danger that lay beneath the apologetic veneer: a figure that a Greco-Roman audience could potentially identify as a tyrant. I analyze Josephus’ account of King David under the rubric of four common Greco-Roman typologies of the stock tyrant, showing that several stories of David conform in many respects to the tyrannical stereotype. Even Josephus’ own alterations, omissions, and additions to the scriptural accounts of David could, at times, have unintentionally worked counter to his apologetic agenda and reinforced a reading of David as a tyrannical figure. Survey of tyrants in Greco-Roman literature confirms my reading as a real possibility, while parallels between David and Herod in Antiquities cement the threat of Josephus’ readers parting ways with his apologetic efforts to present David as the most admirable of kings.